Molecular epidemiological of extended-spectrum β-lactamase producing Escherichia coli isolated in Djibouti - Plantamura, Julie; Bousquet, Aurore; Védy, Serge; Larréché, Sébastien; Bigaillon, Christine; Delacour, Hervé; Mérens, Audrey (The Journal of Infection in Developing Countries, 2019)
Introduction: While the molecular epidemiology of extended-spectrum-b-lactamase (ESBL)-producing E. coli is well known in Europe due to effective surveillance networks and substantial literature, data for Africa are less available, especially in Djibouti. Methodology: We studied 31 isolates of ESBL-producing E. coli from Djibouti and compared these molecular results with data available in Africa. Results: Susceptibility rates were 3.2% for ceftazidim, 48.4% for piperacillin-tazobactam, 90.3% for amikacine and 16.1% for ofloxacin. No isolate showed resistance to carbapenems or colistin. 30 E. coli (96.8%) were positive to blaCTX-M-15, 1 (3.2%) to blaCTX-M-14 and 10 (32.3%) to narrow-broad-spectrum blaTEM. No blaSHV were detected. Fluoroquinolone resistance analysis showed that 30 ofloxacin-resistant E. coli had the mutation Ser-83->Leu on the gyrA gene. 24 E. coli (77.4%) harboured the plasmid-borne aac(6 ')-Ib-cr gene. No E. coli carried the genes qnrA, qnrB and qepA. 10 isolates (32.3%) belonging to the ST131 clone. The plasmid incompatibility group most widely represented in our collection was IncFIA/IB/II. Conclusions: There is no major difference with African epidemiology. In particular, we notice the international diffusion of specific clonal group ST131.